(untitled) (Community Based Medical Journal, 2026)
Abortion remains a major public health concern, particularly in low- and middle-income countries, where limited access to safe abortion services and post-abortion care contributes significantly to maternal morbidity and mortality. Unsafe and delayed abortions continue to place a substantial burden on healthcare systems and communities. A retrospective, observational study was conducted in the Department of Obstetrics & Gynaecology, Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, between January and December of 2024, to assess the demographic, clinical, and outcome profiles of abortion cases managed in the hospital. Clinical records of 100 women who underwent either medical or surgical abortion were recorded in the data sheet and analyzed. Our study revealed that most of the patients were in their mid-reproductive years, with a majority being multiparous and from low socioeconomic backgrounds. Contraceptive use was low, and delayed care-seeking was common. Incomplete abortion was the most frequent clinical type. Major complications included hemorrhage, infection, and sepsis. 4% maternal mortality was observed. Fetal outcomes revealed low birth weight in 38%, preterm birth in 35%, stillbirth 20% cases and live birth was recorded in only 7% cases. Data derived from such a community based setting can guide national strategies to improve reproductive health outcomes. CBMJ 2026 January: vol. 15 no. 01 P:148-154